Factores culturales que influyen en la utilización de anticonceptivos en mujeres indígenas que acuden al servicio de ginecología del Hospital Alfredo Noboa Montenegro, periodo octubre 2024 - mayo 2025. - Medina Vargas, Karla Daniela (2024)
Introduction: The use of contraceptive methods in indigenous women is influenced by cultural factors such as beliefs and traditions, which generate significant barriers to their access and use. These limitations are related to sociocultural norms, misinformation and fear of side effects, which restrict women's autonomy in making decisions about their reproductive health. Objective: To analyze the cultural factors that influence the use of contraceptives in indigenous women who attend the gynecology service of the Alfredo Noboa Montenegro Hospital, during the period from October 2024 to May 2025. Methodology: The survey of women treated at the Alfredo Noboa Montenegro Hospital was used as a technique and through non-probabilistic convenience sampling, a group of 50 indigenous women who attend the gynecology service of this hospital was selected as a sample. The survey technique was carried out using a questionnaire developed by Punina and Moyano (2024) as a collection instrument. Conclusions: Preliminary findings suggest that cultural beliefs, gender roles, and misinformation play a crucial role in the low acceptance and use of contraceptive methods among indigenous women. These factors limit their access to reproductive health services and reinforce existing sociocultural barriers. Understanding these influences is essential to design intervention strategies that respect the customs of these communities, promoting their autonomy and well-being in the area of sexual and reproductive health.